2009
DOI: 10.1111/j.1440-1746.2009.05841.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B infection in an Australian antenatal population: seroprevalence and opportunities for better outcomes

Abstract: It is clear that chronic HBV infection is prevalent in the antenatal population. However, there are no strategies to ensure that infected mothers subsequently undergo further education for HBV or evaluation of infectivity. Clearly strategies are required to ensure improved follow up of hepatitis B infected mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Barriers identified by general practitioners include stigma, poor community knowledge associated with the disease, restrictions on antiviral prescribing, competing health priorities, time pressures and lack of support for contact tracing of diagnosed individuals 31–33 . While systematic population screening occurs in women during antenatal care, women, their children and family members are often not followed up appropriately during pregnancy or following delivery 34–36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers identified by general practitioners include stigma, poor community knowledge associated with the disease, restrictions on antiviral prescribing, competing health priorities, time pressures and lack of support for contact tracing of diagnosed individuals 31–33 . While systematic population screening occurs in women during antenatal care, women, their children and family members are often not followed up appropriately during pregnancy or following delivery 34–36 …”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] While systematic population screening occurs in women during antenatal care, women, their children and family members are often not followed up appropriately during pregnancy or following delivery. [34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…Compliance appears to be high, with approximately 97% of obstetricians self-reporting they always screen for HBV;16 however, a 2003–2006 study indicated poor subsequent management of mothers found to be HBsAg positive 17. Among 295 HBsAg-positive mothers, 78% had previously documented HBsAg, but none had received education on HBV transmission and 93% had no documentation of referral or follow-up plans 17…”
Section: Hbv In Pregnancy: Evidence and Recommendations Of Antenatal mentioning
confidence: 99%
“…A recent study of children in NSW comparing notifications of CHB with the number of children seen at specialist clinics found that 851 of 930 notified infected children were not referred for specialist care, indicative of missed opportunities for early intervention 9 . A similarly concerning disparity between case detection and appropriate management was reported for women diagnosed on antenatal screening at two Sydney tertiary hospitals 10 . This study found no evidence of any hepatitis service involvement in 93% of women diagnosed with CHB during pregnancy.…”
mentioning
confidence: 57%
“…The predominance of females notified in the age groups 20–24 and 25–29 years was unexpected and likely reflects the detection of HBsAg as a result of antenatal screening. The fact that screening could lead to an excess of Victorian female cases when compared to male cases in 20–29 age‐group – contradicting the expectation for a male predominance of CHB – suggests that targeted screening can improve the detection of disease 10 . A study of antenatal women from central Sydney between 1996 and 1999 resulted in an overall HBsAg seroprevalence of 1.5% 2 .…”
Section: Discussionmentioning
confidence: 99%